Relationship Between Maternal Parenting Practices and Risk of Stunting in Toddlers Aged 12–59 Months in Talagasari, Tasikmalaya - Rosye Syifa Fadillah; Ade Kurniawati; Sri Wahyuni Sundari; Meti Patimah; Rissa Nuryuniarti (Pakis Journal Institute, 2026)
Stunting is chronic nutritional problem that impacts physical growth, cognitive development, learning abilities, and future productivity. Among the indirect factors suspected to influence this is maternal parenting, especially for toddlers aged 12–59 months who are in a period of active growth. This study seeks to examine the association between maternal caregiving practices and stunting in Talagasari Village, within the Kawalu Community Health Center, Tasikmalaya City. The study used a quantitative method with a cross-sectional design and involved 82 respondents selected using a purposive sampling technique. Data were collected using a maternal parenting questionnaire and toddler anthropometric data from the Integrated Health Post (Posyandu), then analyzed using the Chi-square test at significance level of p < 0.05. Results showed that the majority of mothers had good parenting patterns (91.5%), while the remainder had adequate parenting patterns (8.5%). In addition, the majority of toddlers did not suffer from stunting (78.0%), while 22.0% experienced stunting. The statistical test results showed p-value of 0.162 (p > 0.05), indicating no significant association between maternal parenting patterns and stunting. This finding indicates that stunting is triggered by various other factors, such maternal nutritional status during pregnancy, socioeconomic conditions, recurrent infectious diseases, environmental sanitation, and long-term nutritional adequacy. Therefore, stunting prevention requires a comprehensive approach through nutrition education, improved sanitation, family support, and cross-sector collaboration.